2019
DOI: 10.1021/acsnano.8b09277
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Focused Ultrasound-Responsive Phase-Transitional Nanoparticles for Thrombolysis without Vascular Damage: A Synergistic Nonpharmaceutical Strategy

Abstract: Multimodal molecular imaging has shown promise as a complementary approach to thrombus detection. However, the simultaneous noninvasive detection and lysis of thrombi for cardiovascular diseases remain challenging. Herein, a perfluorohexane (PFH)-based biocompatible nanostructure was fabricated, namely, as-prepared Fe3O4-poly­(lactic-co-glycolic acid)-PFH-CREKA nanoparticles (NPs), which combine phase transition (PT) thrombolysis capabilities with properties conducive to multimodal imaging. This well-developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
118
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 47 publications
2
118
0
Order By: Relevance
“…Nanodroplets (NDs) are an ultrasound contrast agent, which has recently been applied not only for enhanced ultrasound imaging, but for enhanced drug delivery and more recently, sonothrombolysis of retracted clots [20][21][22][23][24] . Upon insonation with sufficient PNPs, nanodroplets are able to transition from liquid droplets to gas-filled bubbles, which then have similar acoustic properties and behaviors as MBs.…”
Section: Nanodroplet-mediated Sonothrombolysismentioning
confidence: 99%
“…Nanodroplets (NDs) are an ultrasound contrast agent, which has recently been applied not only for enhanced ultrasound imaging, but for enhanced drug delivery and more recently, sonothrombolysis of retracted clots [20][21][22][23][24] . Upon insonation with sufficient PNPs, nanodroplets are able to transition from liquid droplets to gas-filled bubbles, which then have similar acoustic properties and behaviors as MBs.…”
Section: Nanodroplet-mediated Sonothrombolysismentioning
confidence: 99%
“…Anaplastic thyroid carcinoma (ATC) is one of the most malignant carcinomas, though it is comparatively rare, characterized by fast proliferation, neck invasion, and remote metastasis (Zhu et al, 2018;Zhong et al, 2019;Zhou et al, 2019;. The severe prognosis that accompanies ATC is due to the rapid progression of tumors before diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…12 The homing ability of CREKA (and derivatives) has been exploited as the means to direct nanostructures towards targeting specific cell lines and to enhance the nanoconstructs selectively to specific targets, that have been demonstrated both in vitro and in vivo. 15,16 Most studies were focused on probing and imaging tumours sites in sick organisms, maximizing the accumulation of nano-constructs in the targeted locations. [17][18][19] However, its use as part of cytotoxic constructs, that were built to kill specific cell lines, revealed that in most cases the destruction of tumours is preceded by the self-assembly of those nanostructures on target.…”
Section: Introductionmentioning
confidence: 99%
“…20 Despite the advantages of accumulating large amounts of active probes on tumoral tissue, the potential pathologic adverse effects due to the complexity of peptide fibrogenesis has not yet been addressed. Even though, some indirect evidence suggests that the aggregation of the peptide core does not correlate to cell death, 16,19,21 no clear demonstration of its influence over this process has been provided neither its effects to long term exposure. 16,19 Another example of unknown effects of nanoparticles assembly over the cytotoxicity of the constructs is found when building nanoparticles by encapsulating CREKA based peptides in matrices build on the conducting polymer poly(3,4-ethylenedioxythiophene) (PEDOT).…”
Section: Introductionmentioning
confidence: 99%